The First International Conference on Advances in Computational Science and Engineering (ICACSE 2020). Issue 1 (July 2021) - Loganathan, K; Mohanraj, M; Sakthivel, P; Sivakumar, M
Abstract: The First International Conference on Advances in Computational Science and Engineering (ICACSE 2020) on December 25 & 26th, 2020 which is planned to be held at Coimbatore, India. As the covid-19 pandemic spreads endless, according to the direction received from the government and suggestions received from some participants, the organizing committee decided to convert ICACSE 2020 into a fully virtual mode conference. ICACSE 2020 conference was organized by the Live4Research Institute of Research and Development, India . The main objective of the conference is to provide a platform for researchers, professors, and engineers to share their contributions to recent trends and developments in Engineering and Sciences. The scientific event brings together more than 300 researchers. Initially, the conference structure was divided into oral presentations and keynote speeches. In the oral presentations, some scholars' papers were selected as excellent papers, were given about 5-10 minutes to present their oral presentations one by one. Then the keynote speakers were each allocated 30-45 minutes for their plenary talks. We have received tremendous response from all over India and overseas (Malaysia, Oman, Ethiopia, Peru, Columbia, USA). Through a rigorous peer-review process, all submissions were performed double blind review to check their quality of content, level of innovation, significance, originality, and readability. Based on the expertise review comments, only 295 papers were accepted, and the corresponding authors were invited to submit their papers for final publication. The accepted papers are published by IOP Conference Series "Journal of Physics: Conference Series (JPCS)" . The conference proceeding is a compilation of the accepted papers and represents an interesting outcome of the conference. This proceeding covers six chapters: 1. Advances in Computational Mathematical Sciences 2. Advances in Computational Physics and Material Sciences 3. Advances in Computer Science Engineering 4. Advances in Computational Electrical Engineering 5. Advances in Computational Electronics and Communication Engineering 6. Advances in Computational Civil Engineering we would like to thank the keynote speakers, authors, and listeners for their excellent contributions. We wish to extend our sincere gratitude to the organizing committee, reviewers, and volunteers for their constant support. We greatly acknowledge our technical partner Cloudin Software Tech Labs Pvt. Ltd, Coimbatore, India for their effort in publicity and promotion of the conference. We greatly acknowledge all of those who supported ICACSE 2020. The support and contribution of each individual and institution were the backbones of the conference. In specific, we would like to extend our privilege to thank the organizing committee for its valuable inputs in steering the conference program to attain a grand success and reviewing the submitted papers. List of COMMITTEE and logos are available in this pdf.